Dimethyl sulfoxide/oxalyl chloride: A useful reagent for sulfenyletherification. Issue 21 (2nd November 2018) - Gao, Yang; Cheng, Siwei; Zhang, Ting; Ding, Rui; Liu, Yongguo; Sun, Baoguo; Tian, Hongyu
Abstract: A facile method for the sulfenyletherification of unsaturated alcohols using dimethyl sulfoxide/oxalyl chloride has been described in this article. Methanesulfenyl chloride is supposed to be the compound responsible for the sulfenyletherification, which is generated by the reaction of oxalyl chloride with 2 equivalents of dimethyl sulfoxide. The formation pathway of methanesulfenyl chloride is discussed based on the formation of cyclic acetals. Graphical Abstract: